STRUKTUR MODAL: PENGUJIANPECKING ORDER THEORYPADA SIKLUS HIDUPPERUSAHAANGROWTHDANMATURE - Putri Ekawati Darma (Jurnal Manajemen Sinergi, 2015)
This study examine whether growth and mature firms in the manufacturing sectorof Indonesia follow the pecking order theory.Furthermore, the company researchedwhether thestrongergrowthtendsto followthe pecking ordertheorythanmature. The sampleswerecompaniesin themanufacturing industry2007-2011.Hypothesis testingusing multiple regression analysisandaugmentedmodels.Based on classification, classification companies growth tends to more thanmature. The result analysis shows company growth experienced deficiency cash greater than thatmature. Analysis of the results also indicated that group of the company which follows pecking ordertheory is a company growth. It is shown from a correlation between deficiency cash with additionaldebt new issue. These results indicated by a coefficient deficit squared is negative and deficit ispositive.  While based on analysis to the company mature exhibit no pecking order theory becausethe result of testing no significant. Based on the findings, it isconcluded that group of the companyeconomic growth experienced a shortage of cash greater than that of mature. The Group ofcompanies that follow the pecking order theory is the company growth. Group of the company growthalso tend more strong follow pecking order theory than mature.